DISEÑO DE UN SISTEMA CONTABLE EN LA EMPRESA “MATICES COLOR” DE LA CIUDAD DE LOJA. PERIODO: ABRIL – JUNIO DEL 2016 - Maza Gordillo, Irma Alexandra (2017)
The work of thesis whose title is "Design of an Accounting System in the Enterprise" MATICES COLOR "of the City of Loja. Period: April - June 2016 ", its commercial activity is the purchase and sale of retail paints; Is aimed at proposing accounting tools that facilitate the owner of the company to generate reliable information to improve the economic performance of the company. As planned for the design of an accounting system, each of the specific objectives was met; The same one that began with the drawing up of an initial inventory through the physical verification of the goods, values and obligations that the company owns and with these data the Initial State of Situation was carried out, the design of auxiliary purchases, Sales, accounts payable, role of payments and role of provisions that was made with the documentation granted by the owner; Was designed the plan and manual of accounts according to the needs of the company with its description and its respective codification facilitating the correct registration of operations; Subsequently for the development of the accounting process from the Initial inventory to the Financial Statements, a Daily Book was prepared in which the transactions were recorded in an orderly and systematic manner and the Multiple Account System was applied for the correct control of the merchandise account; Then the 5 General Ledger of each of the accounts resulting from the Journal was continued, to continue with the Check Balance, Worksheet, Financial Statements such as: Income Statement, Statement of Financial Position and Cash Flow Statement; Where the economic results obtained in the quarter are clearly and real. Finally, the Financial Indicators of liquidity, activity and indebtedness were applied, thus evaluating the economic and financial situation of the commercial company. It concludes the Thesis demonstrating the reality and the need to Implement the Design of an Accounting System in the Company "Matices Color", the same one that through its correct use is a guide to improve the organization and administration of the company, reason for Which is recommended to its owner to apply the accounting system, in order to strengthen the company in the accounting and financial field and can make good decisions for your business and thus obtain greater economic benefits.